Homeland Security: Establishment and Implementation of Northern Command - Bolkcom, Christopher; DeSerisy, Lloyd; Kapp, Lawrence (Library of Congress. Congressional Research Service., 2003)
Report on the Department of Defense's (DoD) establishment of U.S. Northern Command (NORTHCOM) advancements in fighting terrorism, as well as the issues of NORTHCOM's relationship with other agencies within the DoD.